Russell Armistead G. Assessment of biomass burning emissions and their impacts on urban and regional PM2.5: A Georgia case study - Di* Tian; Yongtao Hu; Yuhang Wang; BoylanJames W; Mei* Zheng (Environ. Sci. Technol., 2009)
Biomass burning is a major and growing contributor to particulate matter with an aerodynamic diameter less than 2.5 μm (PM2.5). Such impacts (especially individual impacts from each burning source) are quantified using the Community Multiscale Air Quality (CMAQ) Model, a chemical transport model (CTM). Given the sensitivity of CTM results to uncertain emission inputs, simulations were conducted using three biomass burning inventories. Shortcomings in the burning emissions were also evaluated by comparing simulations with observations and results from a receptor model. Model performance improved significantly with the updated emissions and speciation profiles based on recent measurements for biomass burning: mean fractional bias is reduced from 22% to 4% for elemental carbon and from 18% to 12% for organic matter; mean fractional error is reduced from 59% to 50% for elemental carbon and from 55% to 49% for organic matter. Quantified impacts of biomass burning on PM2.5 during January, March, May, and July 2002 are 3.0, 5.1, 0.8, and 0.3 μg m−3 domainwide on average, with more than 80% of such impacts being from primary emissions. Impacts of prescribed burning dominate biomass burning impacts, contributing about 55% and 80% of PM2.5 in January and March, respectively, followed by land clearing and agriculture field burning. Significant impacts of wildfires in May and residential wood combustion in fireplaces and woodstoves in January are also found.